Retinal fluid is associated with cytokines of aqueous humor in age-related macular degeneration using automatic 3-dimensional quantification - Song, Siyuan; Jin, Kai; Wang, Shuai; Yang, Ce; Zhou, Jingxin; Chen, Zhiqing; Ye, Juan (Frontiers in Cell and Developmental Biology, 2023)
Background: To explain the biological role of cytokines in the eye and the possible role of cytokines in the pathogenesis of neovascular age-related macular degeneration (nAMD) by comparing the correlation between cytokine of aqueous humor concentration and optical coherence tomography (OCT) retinal fluid. Methods: OCT images and aqueous humor samples were collected three times from each of the 20 nAMD patients. Retinal fluid volume in OCT was automatically quantified using deep learning. Twenty-eight cytokines were detected in aqueous humor using the Luminex technology. OCT fluid volume measurements were correlated with changes in aqueous humor cytokine levels using Pearson's correlation coefficient (PCC). Results: The patients with intraretinal fluid (IRF) showed significantly lower levels of cytokines, such as C-X-C motif chemokine ligand 2 (CXCL2) (p=0.03) and CXCL11 (p=0.009), compared with the patients without IRF. And the IRF volume was negatively correlated with CXCL2 (r=－0.407, p=0.048) and CXCL11 (r=－0.410, p=0.046) concentration in the patients with IRF. Meanwhile, the subretinal fluid (SRF) volume was positively correlated with vascular endothelial growth factor (VEGF) concentration (r=0.299, p=0.027) and negatively correlated with interleukin (IL)-36β concentration (r=－0.295, p=0.029) in the patients with SRF. Conclusion: Decreased level of VEGF was associated with decreased OCT-based retinal fluid volume in nAMD patients, while increased levels of CXCL2, CXCL11 and IL-36β were associated with decreased OCT-based retinal fluid volume in nAMD patients, which may suggest a role for inflammatory cytokines in retinal morphological changes and pathogenesis of nAMD patients.